Analysis of risk indicators for prevalence of peri-implant diseases in Turkish population - Sadiye Gunpinar; Bilge Meraci; Mert Karas (SpringerOpen, 2020)
Abstract Background The aim of this cross-sectional study was (1) to determine the prevalence of peri-implant mucositis and peri-implantitis and (2) to reveal the risk indicators associated with peri-implant diseases. The second point was to investigate the role of keratinized mucosa on peri-implant health. Materials and methods Three hundred and eighty-two subjects who were treated with 1415 dental implants between 2011-2017 were clinically evaluated. Patients' medical and dental history, as well as implant details, were recorded. Peri-implant examination included probing pocket depth (PPD), bleeding on probing (BoP), plaque index (PI), gingival index (GI), and keratinized tissue width. Furthermore, the patient (sex, age, and smoking) and implant/prosthesis-related factors (surface characteristic, time in function, design of prosthesis etc.) were evaluated. Implants were classified into three groups: healthy, peri-implant mucositis, and peri-implantitis. Uni- and multi-variate regression analyses were utilized for statistics. Results 41.1% (n = 157) and 36.9% (n = 84) of patients had mucositis and peri-implantitis, respectively. 53.6% (n = 758) of implants (95%CI 80.2-90.4) had mucositis, and 21.7% (n = 307) had peri-implantitis. Patients with a maintenance < 2/year (OR = 2.576), having periodontitis (OR = 3.342) and higher PI (OR = 3.046) had significant associations with the development of peri-implant mucositis. Significant ORs were determined for peri-implantitis with patients having maintenance < 2/year (OR = 2.048), having number of implants ≥ 4 (OR = 2.103), diagnosed with periodontitis (OR = 3.295), and higher PI (OR = 7.055). Keratinized tissue width < 2 mm (ORs = 5389/8.013), PPD (ORs = 1.570/8.338), PI (ORs = 6.726/5.205), and BoP (ORs = 3.645/4.353) independent variables were significantly associated with both peri-implant mucositis and peri-implantitis at implant level, respectively. Conclusions Within the limits of this study, the prevalence of mucositis and peri-implantitis was shown to be high in Turkish population. Furthermore, increased risk for peri-implantitis was identified in patients having maintenance < 2/year, presence of periodontitis, poor plaque control, and having number of implants ≥ 4. Less keratinized tissue (< 2 mm), PPD, and BoP were also risk indicators for peri-implantitis development.